Strategi Koping Dan Dukungan Keluarga Dengan Kecemasan Pasien Pre Op Sectio Caesarea - Ika Suhartanti; Yulia Nur Aini; Henry Sudiyanto (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Sectio caesarea was a surgical procedure that often caused psychological responses, particularly preoperative anxiety. This anxiety was an anticipatory response to perceived threats and could be influenced by coping strategies and family support. This study aimed to determine the relationship between coping strategies and family support with anxiety levels in preoperative sectio caesarea patients. This study employed a cross-sectional design conducted at Arafah Anwar Medika Hospital, Sidoarjo. A total of 35 respondents were selected using purposive sampling. Data were collected using the Brief COPE questionnaire, family support questionnaire, and the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data analysis was performed using the Spearman rho test. The results showed that most respondents had adaptive coping strategies (57.1%), while nearly half had moderate family support (42.9%) and moderate anxiety levels (37.1%). Statistical analysis indicated a significant relationship between coping strategies and anxiety levels (p < 0.05; r = -0.718), as well as between family support and anxiety levels (p < 0.05; r = -0.825). Adaptive coping strategies and higher family support were associated with lower anxiety levels in preoperative sectio caesarea patients. Strengthening psychological support and involving family members were essential to reduce patient anxiety before surgery.